Spatial Analysis of Childhood Tuberculosis in Boyolali Regency - Nugraha, Rendra Putra; Setiyadi, Noor Alis (Journal La Medihealtico, 2025)
Childhood tuberculosis (TB) in Boyolali Regency has shown a significant increase. Spatial analysis research has not previously been conducted in Boyolali, which prompted the researcher to investigate and analyze the spatial distribution patterns and clusters of childhood TB cases. This study employs a quantitative descriptive design and was conducted in the working area of the Boyolali Regency Health Office from March to June 2025. Sampling techniques involved secondary data geospatial collection, the use of geographic coordinates of primary health center administrative areas, and Google Earth. The data population included childhood TB cases in Boyolali Regency from 2021 to 2023, along with data on total population, population density, and BCG immunization coverage. The research instrument used a secondary data recording table. Data analysis was performed using QGIS and SaTScan software. The results identified significant clusters in the central and southern regions, particularly in the working areas of Boyolali 1 & 2, Mojosongo, Teras, and Banyudono health centers. Spatially, population density was found to influence the incidence of childhood TB cases, whereas BCG immunization coverage was not sufficient to suppress incidence rates.